Theory of economy as the original cause of the world crisis - Witold Jakóbik (Contemporary Economics, 2011)
A growing debate around the active role played by the neoliberal ideology and the economy connected with it in the crisis development. The polarisation of researchers in this area is quite significant: starting from the negation of this role to its complete affirmation. This analysis is aimed at contributing to the aforementioned debate, putting forward the following hypothesis: historical development of mainstream economics and its influence, to a considerable extent, determined the outbreak of the large-scale crisis. In the analytic part, I look into some aspects of economic methodology, both orthodox and heterodox, taking my own position on the basis of important literature. Criticism of the traditional paradigm and a review of innovative trends in research do not show a straightforward road, however, which imposes a moderately optimistic outlook on the future, especially as regards the application value of the theory of economy.
Keywords: A11; B22; G01; 330; global crisis; methodology of economy; traditional and new paradigm